Hard Enough to Manage My Emotions: How Hardiness Moderates the Relationship Between Emotional Demands and Exhaustion - Mazzetti, Greta; Guglielmi, Dina; Topa, Gabriela (Frontiers in Psychology, 2020)
The frequency of conflicts with patients' families is one of the main contributors to the amount of emotional demands that healthcare professionals must tackle to prevent the occurrence of burnout symptoms. On the other hand, research evidence suggests that hardiness could enable healthcare professionals to handle their responsibilities and problems effectively. Based on the health impairment process of the Job Demands-Resources model, the main goal of this study was to delve deeper into the relationship between conflict with patients’ families, emotional demands and exhaustion, as well as to test the buffering role of hardiness. Data were collected on a sample of N= 295 healthcare professionals working in a private hospital in Northern Italy. Most of them were women (78.6%) with a mean age of 40.62 years (SD = 9.50). The mediation of emotional demands within the association between conflict with families and emotional exhaustion and the moderating role of hardiness were tested using a bootstrapping approach. In the current sample, emotional demands mediated the association between conflict with families and exhaustion among healthcare professionals. Moreover, this relationship decreased among individuals with higher levels of hardiness. These findings contribute to the current understanding of the negative impact played by conflict with families on healthcare professionals' psychological wellbeing. Furthermore, they corroborated the role of hardiness as a personal resource that could prevent the occurrence of burnout symptoms. In addition to manage – and decrease – episodes of conflict with patients and their families, organizations in the healthcare sector should develop interventions aimed at fostering employees' hardiness and, consequently, tackle job demands ingrained in their profession (i.e., emotional demands).